Ranging pattern and population estimates of tupaia and calosciusrus in peatswamp forest in Unimas - Fadzilawati Zahrah, Hamdan. (Universiti Malaysia Sarawak (UNIMAS), 2004)
The home range of Tupaia and Calloscillrtls at UNIMAS peat swamp forest were studied using mark recapture method. Two sampling period of 20 days each was done to gather all the data on the home range. The first ampling time was from 5th July 2003 to 24th July 2003 and continued with the second sampling on the 13th September 2003 until 2nd October 2003. The purpose of this study is to make baseline information for the study of ranging pattern made by small mammals. A population estimates was also done as supplementary information in the research. Minimum Convex Polygon (MCP) is used in calculating the home range size. Three models of estimating the population were applied in this study, namely the Lincoln-Petersen, the Schnabel, and the Schumacher and Eschmeyer methods. Throughout the research, 22 totals of individuals of 11 males and 11 females were captured using cage trap. Species captured are the Calloscillrus notatlls, Calloscillrus prevostii borneensis, Callosciurus prevostii sanggaus, Tllpaia tana and TlIpaia picta. Banana is the most favorable baits use for capturing small mammals.